Зарни чорыг: повестьёс, веросъёс / Петр Куликов - Куликов Петр Васильевич (Удмуртия, 1992)
Экземпляры: ф.10 (1992) / Инвентарный номер: 35822 / Цена: / Сис.шифр: 84(2Рос=Удм)6-4 / Авт.знак: К 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Удм)6-44